A Function Private Attribute-Based Encryption. (23rd January 2014) - Han, Fei; Qin, Jing
The function privacy notion was proposed by Boneh, Raghunathan, and Segev in August 2013. It guarantees that the secret key reveals nothing to malicious adversary, beyond the unavoidable minimal information such as the length of ciphertext. They constructed a function private identity-based encryption that contains equality functionality. In this work we construct a new function private attribute-based encryption which supports more complex functionality. And we transform it to a searchable encryption. In searchable encryption, the trapdoor of searching keywords can be seen as the secret key. Hence, using this system can efficiently resist keyword guessing attack.